2019
DOI: 10.1007/s42452-019-0205-1
|View full text |Cite
|
Sign up to set email alerts
|

Efficient synthesis of alkynyl carbon materials derived from CaC2 through solvent-free mechanochemical strategy for supercapacitors

Abstract: The synthesis of new carbonaceous electrode materials for supercapacitors and the discovery of efficient techniques for the CaC 2 activation are meaningful subjects. In this study, unique alkynyl carbon materials (ACMs) were effectively synthesized through solvent-free mechanochemical reactions of CaC 2 with C 2 Cl 6 or C 6 Br 6. Their components and structure were comprehensively characterized, and their supercapacitor performances were examined in detail. The mechanochemistry has proved to be an efficient an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Considering its positive charge on the carbon atom, CO 2 may react favorably with carboanion chemicals. In this regard, calcium carbide (CaC 2 ) may be a good candidate due to its abundant [CC] 2– anions and cost effectiveness as a bulk chemical, and an alkynyl carbon material may be fabricated via successive nucleophilic substitution reactions. However, the crystalline structure of CaC 2 greatly limits its reactivity under normal conditions. Therefore, CaC 2 is mostly used as raw material for the acetylene industry, resulting in a huge energy waste due to the high energy consumption in its manufacture (CaO + C → CaC 2 + CO, Δ H = +465.7 kJ/mol) but high energy release in its hydrolysis (CaC 2 + H 2 O → C 2 H 2 + Ca­(OH) 2 , Δ H = −120 kJ/mol). , To liberate its reactivity, mechanochemistry may be viable, which has been successfully used in synthesing alkynyl carbon materials, , solid based reactions, and gaseous reactant activations . Meanwhile, the reactivity of CO 2 can be also improved under mechanochemical treatment owing to its widely applicable manner for the reactive activation of solids, liquids, and even gases. For example, high-quality edge-carboxylated graphene can be efficiently synthesized by a simple ball milling of graphite in the presence of CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Considering its positive charge on the carbon atom, CO 2 may react favorably with carboanion chemicals. In this regard, calcium carbide (CaC 2 ) may be a good candidate due to its abundant [CC] 2– anions and cost effectiveness as a bulk chemical, and an alkynyl carbon material may be fabricated via successive nucleophilic substitution reactions. However, the crystalline structure of CaC 2 greatly limits its reactivity under normal conditions. Therefore, CaC 2 is mostly used as raw material for the acetylene industry, resulting in a huge energy waste due to the high energy consumption in its manufacture (CaO + C → CaC 2 + CO, Δ H = +465.7 kJ/mol) but high energy release in its hydrolysis (CaC 2 + H 2 O → C 2 H 2 + Ca­(OH) 2 , Δ H = −120 kJ/mol). , To liberate its reactivity, mechanochemistry may be viable, which has been successfully used in synthesing alkynyl carbon materials, , solid based reactions, and gaseous reactant activations . Meanwhile, the reactivity of CO 2 can be also improved under mechanochemical treatment owing to its widely applicable manner for the reactive activation of solids, liquids, and even gases. For example, high-quality edge-carboxylated graphene can be efficiently synthesized by a simple ball milling of graphite in the presence of CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The signal for C≡C appeared at ≈2213 cm −1 for N-Gra-3. Owing to the extensively conjugated architecture of N-Gra-3-2, the solid-state 13 C nuclear magnetic resonance ( 13 C NMR) collected by the direct polarization magic-angle spinning (DPMAS) experiment only exhibited a broad peak in the range of 70-200 ppm, including the carbon-carbon triple bonds, aromatic carbon signals, and the moieties including C-N bonds formation (Figure 3I). The morphology characterization of N-Gra-3-2 revealed that the materials were composed of bulk particles with sheet-like structures at the edge sites, as shown in the scanning electron microscopy (SEM) and TEM images (Figure 3J,K).…”
Section: Synthesis Characterization and Supercapacitor Performance Of...mentioning
confidence: 99%
“…Comparatively, the mechanochemistrydriven methods (pathway (3)) could afford graphyne-related materials under neat and ambient conditions by leveraging the energy input from mechanochemical treatment to promote the nucleophilic attack reaction of CaC 2 with multiple substituted aromatic halides. [12][13][14] For example, mechanochemical treatment of CaC 2 and 1,2,4,5-tetrabromobenzene (TBB) mixture could produce graphyne materials via the nucleophilic attack of the electron-rich alkynyl anion on the CBr bond in the TBB monomer. [15] Successive substitution of the CBr bonds on the benzene ring by the alkynyl linkages afforded π-conjugated networks composed of abundant alkynyl moieties and benzene rings.…”
Section: Introductionmentioning
confidence: 99%
“…Under industrial manufacturing conditions, 5 to 20 L of water is used to cool the reaction mixture and prevent polymerization or explosion. Recently, calcium carbide was actively used in the construction of heterocycles [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ], vinylation processes [ 14 , 15 ], synthesis of monomers [ 16 , 17 ], mechanochemical processes [ 18 , 19 , 20 , 21 , 22 ], and many other organic transformations [ 23 , 24 , 25 ]. The key advantage of calcium carbide is its renewable potential [ 26 ].…”
Section: Introductionmentioning
confidence: 99%